Evaluation of salivary parameters and Streptococcus' Mutans count in children with cerebral palsy in Egypt: a case control study - Sara M. Quritum; Amel M. Ali; May M. Raouf; Tarek E. I. Omar; Karin M. L. Dowidar (BMC, 2022)
Abstract Background Children with cerebral palsy (CP) are at high risk for dental caries. Alteration of some salivary properties encountered among them compared to healthy children, could play a role in this elevated risk. Objectives The aim of the present study was to assess salivary physicochemical properties; including total antioxidant (TAC), flow rate, viscosity, pH and buffering capacity, as well as Streptococcus mutans level among children with CP, also to correlate these variables to their caries experience. Materials and methods This case control study included 80 children with CP, study group (SG) and matched number of healthy children for control group (CG). Interview-based questionnaire, clinical examination, salivary biochemical and microbiological investigations using MALDI-TOF were done. Results In SG, the caries experience in primary teeth dmft and S. mutans log value were significantly higher than CG (P = 0.039, P = 0.002) while unstimulated salivary flow rate, buffering capacity and salivary TAC were significantly lower (P < 0.0001). Multivariate linear regression showed that the presence of CP was significantly associated with the greatest variation in caries experience in the primary teeth and permanent teeth. Higher unstimulated salivary flow rate, or an increase in buffering capacity by 1 ml of acid/ml of saliva were associated with lower number of the affected primary and permanent teeth. On the other hand, One-unit increase in S. mutans log count and higher salivary TAC were associated with higher caries experience. Conclusion Children with CP have higher caries experience (dmf) due to lower salivary protective factors and higher S. mutans counts.